Aberrant dependence of default mode/central executive network interactions on anterior insular salience network activity in schizophrenia - Manoliu, Andrei; Riedl, Valentin; Zherdin, Andriy; Muehlau, Mark; Schwerthoeffer, Dirk; Scherr, Martin; Peters, Henning; Zimmer, Claus; Foerstl, Hans; Baeuml, Josef; Wohlschlaeger, Afra M.; Sorg, Christian (Schizophrenia Bulletin, 2014)
In schizophrenia, consistent structural and functional changes have been demonstrated for the insula including aberrant salience processing, which is critical for psychosis. Interactions within and across default mode and central executive network (DMN, CEN) are impaired in schizophrenia. The question arises whether these 2 types of changes are related. Recently, the anterior insula has been demonstrated to control DMN/CEN interactions. We hypothesized that aberrant insula and DMN/CEN activity in schizophrenia is associated with an impaired dependence of DMN/CEN interactions on anterior insular salience network (SN) activity. Eighteen patients with schizophrenia during psychosis and 20 healthy controls were studied by resting-state-fMRI and psychometric examination. High-model-order independent component analysis of fMRI data revealed spatiotemporal patterns of synchronized ongoing blood-oxygenation-level- dependent (BOLD) activity including SN, DMN, and CEN. Scores of functional and time-lagged connectivity across networks' time courses were calculated. Connectivity scores and spatial network maps were compared between groups and related with patients' hallucination and delusion severity. Spatial BOLD-synchronicity was altered in patients' SN, DMN, and CEN, including decreased activity in the right anterior insula (rAI). Patients' functional connectivity between DMN and CEN was increased and related with hallucinations severity. Importantly, patients' time-lagged connectivity between SN and DMN/CEN was reduced, and decreased rAI activity of the SN was associated with both hallucinations and increased functional connectivity between DMN and CEN. Data provide evidence for an aberrant dependence of DMN/CEN interactions on anterior insular SN activity, linking impaired insula, DMN, CEN activity, and psychosis in schizophrenia. © 2013 The Author. Published by Oxford University Press on behalf of the Maryland Psychiatric Research Center. All rights reserved.
CRIS-Team Scopus Importer:2022-11-28
Keywords: anterior insula; central executive network; default mode network; psychosis; salience network; schizophrenia

Aberrant intrinsic connectivity of hippocampus and amygdala overlap in the fronto-insular and dorsomedial-prefrontal cortex in major depressive disorder - Tahmasian, Masoud; Knight, David C.; Manoliu, Andrei; Schwerthoeffer, Dirk; Scherr, Martin; Meng, Chun; Shao, Junming; Peters, Henning; Doll, Anselm; Khazaie, Habibolah; Drzezga, Alexander; Baeuml, Josef; et al. (Frontiers in Human Neuroscience, 2013)
Neuroimaging studies of major depressive disorder (MDD) have consistently observed functional and structural changes of the hippocampus (HP) and amygdale (AY). Thus, these brain regions appear to be critical elements of the pathophysiology of MDD. The HP and AY directly interact and show broad and overlapping intrinsic functional connectivity (iFC) to other brain regions. Therefore, we hypothesized the HP and AY would show a corresponding pattern of aberrant intrinsic connectivity in MDD. Resting-state functional MRI was acquired from 21 patients with MDD and 20 healthy controls. B-Maps of region-ofinterest-based FC for bilateral body of the HP and basolateral AY were used as surrogates for iFC of the HP and AY Analysis of variance was used to compare B-maps between MDD and healthy control groups, and included covariates for age and gender as well as gray matter volume of the HP and AY The HP and AY of MDD patient's showed an overlapping pattern of reduced FC to the dorsomedial-prefrontal cortex and fronto-insular operculum. Both of these regions are known to regulate the interactions among intrinsic networks (i.e., default mode, central executive, and salience networks) that are disrupted in MDD. These results provide the first evidence of overlapping aberrant HP and AY intrinsic connectivity in MDD. Our findings suggest that aberrant HP and AY connectivity may interact with dysfunctional intrinsic network activity in MDD. © 2013 Tahmasian, Knight, Manoliu, Schwerthöffer, Scherr, Meng, Shao, Peters, Doll, Khazaie, Drzezga, Bäuml, Zimmer, Förstl, Wohlschläger, Riedl and Sorg.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Amygdala; Dorsomedial-prefrontal cortex; Fronto-insular operculum; Hippocampus; Intrinsic functional connectivity; Major depressive disorder; Resting-state fMRI

Aberrant topology of striatum's connectivity is associated with the number of episodes in depression - Meng, Chun; Brandl, Felix; Tahmasian, Masoud; Shao, Junming; Manoliu, Andrei; Scherr, Martin; Schwerthoeffer, Dirk; Baeuml, Josef; Foerstl, Hans; Zimmer, Claus; Wohlschlaeger, Afra M.; Riedl, Valentin; et al. (Brain, 2014)
In major depressive disorder, depressive episodes reoccur in ∼60% of cases; however, neural mechanisms of depressive relapse are poorly understood. Depressive episodes are characterized by aberrant topology of the brainvs intrinsic functional connectivity network, and the number of episodes is one of the most important predictors for depressive relapse. In this study we hypothesized that specific changes of the topology of intrinsic connectivity interact with the course of episodes in recurrent depressive disorder. To address this hypothesis, we investigated which changes of connectivity topology are associated with the number of episodes in patients, independently of current symptoms and disease duration. Fifty subjects were recruited including 25 depressive patients (two to 10 episodes) and 25 gender- and age-matched control subjects. Resting-state functional magnetic resonance imaging, Harvard-Oxford brain atlas, wavelet-transformation of atlas-shaped regional time-series, and their pairwise Pearson's correlation were used to define individual connectivity matrices. Matrices were analysed by graph-based methods, resulting in outcome measures that were used as surrogates of intrinsic network topology. Topological scores were subsequently compared across groups, and, for patients only, related with the number of depressive episodes and current symptoms by partial correlation analysis. Concerning the whole brain connectivity network of patients, small-world topology was preserved but global efficiency was reduced and global betweenness-centrality increased. Aberrant nodal efficiency and centrality of regional connectivity was found in the dorsal striatum, inferior frontal and orbitofrontal cortex as well as in the occipital and somatosensory cortex. Inferior frontal changes were associated with current symptoms, whereas aberrant right putamen network topology was associated with the number of episodes. Results were controlled for effects of total grey matter volume, medication, and total disease duration. This finding provides first evidence that in major depressive disorder aberrant topology of the right putamen's intrinsic connectivity pattern is associated with the course of depressive episodes, independently of current symptoms, medication status and disease duration. Data suggest that the reorganization of striatal connectivity may interact with the course of episodes in depression thereby contributing to depressive relapse risk. © 2013 The Author (2013).
CRIS-Team Scopus Importer:2022-11-28
Keywords: graph analysis; intrinsic functional connectivity; major depressive disorder; recurrent episodes; striatum

Asymmetric loss of parietal activity causes spatial bias in prodromal and mild Alzheimer's disease - Sorg, Christian; Myers, Nicholas; Redel, Petra; Bublak, Peter; Riedl, Valentin; Manoliu, Andrei; Perneczky, Robert; Grimmer, Timo; Kurz, Alexander; Foerstl, Hans; Drzezga, Alexander; Mueller, Hermann J.; et al. (Biological Psychiatry, 2012)
Background: In Alzheimer's disease (AD), loss of effective neuronal activity is reflected by cortical glucose hypometabolism. Hypometabolism in the posterior parietal cortex (PPC) is among the first in vivo signs of AD; however, its functional impact on large-scale brain mechanisms and behavior is poorly understood. The lateral PPC contributes to spatial attention constituting a basic function of the human brain. We hypothesized 1) that lateral PPC hypometabolism is associated with impaired spatial attention in very early AD and 2) that impaired competition of effective neuronal activity across hemispheres might underlie this deficit in terms of brain mechanisms. Methods: A model-based imaging approach was applied to assess patients with prodromal (n = 28) and mild (n = 7) AD. Quantitative attention parameters, derived from performance on simple psychophysical tasks and analyzed by Bundesen's computational theory of visual attention, were related to brain metabolism, measured by 18F-fluorodeoxyglucose positron emission tomography. Results: Patients' left and right lateral PPC metabolism was reduced. Nine patients had significant spatial attentional bias on the left side and two patients on the right. Direction and degree of spatial bias was correlated with direction and degree of an interhemispheric metabolism bias in the inferior parietal lobe and temporoparietal junction. Conclusions: Our data provide evidence that in very early AD, asymmetric hypometabolism of the lateral PPC causes spatial attentional bias. Results are broadly consistent with the model that asymmetrically impaired effective neuronal PPC activity in AD biases the competition of visual objects for cortical representation and access to awareness to one side. © 2012 Society of Biological Psychiatry.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Bundesen's theory of visual attention; FDG-PET; model-based imaging; parietal cortex; prodromal Alzheimer's disease; spatial attention

Based on the network degeneration hypothesis: Separating individual patients with different neurodegenerative syndromes in a preliminary hybrid PET/MR study - Tahmasian, Masoud; Shao, Junming; Meng, Chun; Grimmer, Timo; Diehl-Schmid, Janine; Yousefi, Behrooz H.; Foerster, Stefan; Riedl, Valentin; Drzezga, Alexander; Sorg, Christian (Journal of Nuclear Medicine, 2016)
The network degeneration hypothesis (NDH) of neurodegenerative syndromes suggests that pathologic brain changes distribute primarily along distinct brain networks, which are characteristic for different syndromes. Brain changes of neurodegenerative syndromes can be characterized in vivo by different imaging modalities. Our aim was to test the hypothesis whether multimodal imaging based on the NDH separates individual patients with different neurodegenerative syndromes. Methods: Twenty patients with Alzheimer disease (AD) and 20 patients with frontotemporal lobar degeneration (behavioral variant frontotemporal dementia [bvFTD, n 5 11], semantic dementia [SD, n 5 4], or progressive nonfluent aphasia [PNFA, n 5 5]) underwent simultaneous MRI and 18F-FDG PET in a hybrid PET/MR scanner. The 3 outcomemeasureswere voxelwise values of degree centrality as a surrogate for regional functional connectivity, glucose metabolism as a surrogate for regional metabolism, and volumetric-based morphometry as a surrogate for regional gray matter volume. Outcome measures were derived from predefined core regions of 4 intrinsic networks based on theNDH,which have been demonstrated to be characteristic for AD, bvFTD, SD, and PNFA, respectively. Subsequently, we applied support vector machine to classify individual patients via combined imaging measures, and results were evaluated by leave-one-out cross-validation. Results: On the basis of multimodal voxelwise regional patterns, classification accuracies for separating patients with different neurodegenerative syndromes were 77.5% for AD versus others, 82.5% for bvFTD versus others, 97.5% for SD versus others, and 87.5% for PNFA versus others. Multimodal classification results were significantly superior to unimodal approaches. Conclusion: Our finding provides initial evidence that the combination of regional metabolism, functional connectivity, and gray matter volume, which were derived from disease characteristic networks, separates individual patients with different neurodegenerative syndromes. Preliminary results suggest that employing multimodal imaging guided by the NDH may generate promising biomarkers of neurodegenerative syndromes.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Alzheimer's disease; Frontotemporal lobar degeneration; Hybrid PET/MR; Network degeneration hypothesis; Neurodegenerative syndromes

Changes in extra-striatal functional connectivity in patients with schizophrenia in a psychotic episode - Peters, Henning; Riedl, Valentin; Manoliu, Andrei; Scherr, Martin; Schwerthoeffer, Dirk; Zimmer, Claus; Foerstl, Hans; Baeuml, Josef; Sorg, Christian; Koch, Kathrin (British Journal of Psychiatry, 2017)
Background In patients with schizophrenia in a psychotic episode, intra-striatal intrinsic connectivity is increased in the putamen but not ventral striatum. Furthermore, multimodal changes have been observed in the anterior insula that interact extensively with the putamen. Aims We hypothesised that during psychosis, putamen extrastriatal functional connectivity is altered with both the anterior insula and areas normally connected with the ventral striatum (i.e. altered functional connectivity distinctiveness of putamen and ventral striatum). Method We acquired resting-state functional magnetic resonance images from 21 patients with schizophrenia in a psychotic episode and 42 controls. Results Patients had decreased functional connectivity: The putamen with right anterior insula and dorsal prefrontal cortex, the ventral striatum with left anterior insula. Decreased functional connectivity between putamen and right anterior insula was specifically associated with patients' hallucinations. Functional connectivity distinctiveness was impaired only for the putamen. Conclusions Results indicate aberrant extra-striatal connectivity during psychosis and a relationship between reduced putamen-right anterior insula connectivity and hallucinations. Data suggest that altered intrinsic connectivity links striatal and insular pathophysiology in psychosis.
CRIS-Team Scopus Importer:2022-11-28

Changes in resting-state connectivity in musicians with embouchure dystonia - Haslinger, Bernhard; Noe, Jonas; Altenmueller, Eckart; Riedl, Valentin; Zimmer, Claus; Mantel, Tobias; Dresel, Christian (Movement Disorders, 2017)
Objective: Embouchure dystonia is a highly disabling task-specific dystonia in professional brass musicians leading to spasms of perioral muscles while playing the instrument. As they are asymptomatic at rest, resting-state functional magnetic resonance imaging in these patients can reveal changes in functional connectivity within and between brain networks independent from dystonic symptoms. Methods: We therefore compared embouchure dystonia patients to healthy musicians with resting-state functional magnetic resonance imaging in combination with independent component analyses. Results: Patients showed increased functional connectivity of the bilateral sensorimotor mouth area and right secondary somatosensory cortex, but reduced functional connectivity of the bilateral sensorimotor hand representation, left inferior parietal cortex, and mesial premotor cortex within the lateral motor function network. Within the auditory function network, the functional connectivity of bilateral secondary auditory cortices, right posterior parietal cortex and left sensorimotor hand area was increased, the functional connectivity of right primary auditory cortex, right secondary somatosensory cortex, right sensorimotor mouth representation, bilateral thalamus, and anterior cingulate cortex was reduced. Negative functional connectivity between the cerebellar and lateral motor function network and positive functional connectivity between the cerebellar and primary visual network were reduced. Conclusions: Abnormal resting-state functional connectivity of sensorimotor representations of affected and unaffected body parts suggests a pathophysiological predisposition for abnormal sensorimotor and audiomotor integration in embouchure dystonia. Altered connectivity to the cerebellar network highlights the important role of the cerebellum in this disease. © 2016 International Parkinson and Movement Disorder Society.
CRIS-Team Scopus Importer:2022-11-28
Keywords: dystonia; fMRI; functional connectivity; musician; resting-state

Cognitive emotion regulation enhances aversive prediction error activity while reducing emotional responses - Mulej Bratec, Satja; Xie, Xiyao; Schmid, Gabriele; Doll, Anselm; Schilbach, Leonhard; Zimmer, Claus; Wohlschlaeger, Afra; Riedl, Valentin; Sorg, Christian (NeuroImage, 2015)
Cognitive emotion regulation is a powerful way of modulating emotional responses. However, despite the vital role of emotions in learning, it is unknown whether the effect of cognitive emotion regulation also extends to the modulation of learning. Computational models indicate prediction error activity, typically observed in the striatum and ventral tegmental area, as a critical neural mechanism involved in associative learning. We used model-based fMRI during aversive conditioning with and without cognitive emotion regulation to test the hypothesis that emotion regulation would affect prediction error-related neural activity in the striatum and ventral tegmental area, reflecting an emotion regulation-related modulation of learning. Our results show that cognitive emotion regulation reduced emotion-related brain activity, but increased prediction error-related activity in a network involving ventral tegmental area, hippocampus, insula and ventral striatum. While the reduction of response activity was related to behavioral measures of emotion regulation success, the enhancement of prediction error-related neural activity was related to learning performance. Furthermore, functional connectivity between the ventral tegmental area and ventrolateral prefrontal cortex, an area involved in regulation, was specifically increased during emotion regulation and likewise related to learning performance. Our data, therefore, provide first-time evidence that beyond reducing emotional responses, cognitive emotion regulation affects learning by enhancing prediction error-related activity, potentially via tegmental dopaminergic pathways.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Aversive conditioning; Reappraisal; Rescorla Wagner rule; Ventral tegmental area

Cognitive emotion regulation modulates the balance of competing influences on ventral striatal aversive prediction error signals - Bratec, Satja Mulej; Xie, Xiyao; Wang, Yijun; Schilbach, Leonhard; Zimmer, Claus; Wohlschlaeger, Afra M.; Riedl, Valentin; Sorg, Christian (NeuroImage, 2017)
Cognitive emotion regulation (CER) is a critical human ability to face aversive emotional stimuli in a flexible way, via recruitment of specific prefrontal brain circuits. Animal research reveals a central role of ventral striatum in emotional behavior, for both aversive conditioning, with striatum signaling aversive prediction errors (aPE), and for integrating competing influences of distinct striatal inputs from regions such as the prefrontal cortex (PFC), amygdala, hippocampus and ventral tegmental area (VTA). Translating these ventral striatal findings from animal research to human CER, we hypothesized that successful CER would affect the balance of competing influences of striatal afferents on striatal aPE signals, in a way favoring PFC as opposed to ‘subcortical’ (i.e., non-isocortical) striatal inputs. Using aversive Pavlovian conditioning with and without CER during fMRI, we found that during CER, superior regulators indeed reduced the modulatory impact of ‘subcortical’ striatal afferents (hippocampus, amygdala and VTA) on ventral striatal aPE signals, while keeping the PFC impact intact. In contrast, inferior regulators showed an opposite pattern. Our results demonstrate that ventral striatal aPE signals and associated competing modulatory inputs are critical mechanisms underlying successful cognitive regulation of aversive emotions in humans.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Aversive prediction error; Emotion regulation; fMRI; Functional connectivity; Reappraisal ability; Ventral striatum

Coherence of BOLD signal and electrical activity in the human brain during deep sevoflurane anesthesia - Golkowski, Daniel; Ranft, Andreas; Kiel, Tobias; Riedl, Valentin; Kohl, Philipp; Rohrer, Guido; Pientka, Joachim; Berger, Sebastian; Preibisch, Christine; Zimmer, Claus; Mashour, George A.; Schneider, Gerhard; et al. (Brain and Behavior, 2017)
Introduction: Changes in neural activity induce changes in functional magnetic resonance (fMRI) blood oxygenation level dependent (BOLD) signal. Commonly, increases in BOLD signal are ascribed to cellular excitation. Objective: The relationship between electrical activity and BOLD signal in the human brain was probed on the basis of burst suppression EEG. This condition includes two distinct states of high and low electrical activity. Methods: Resting-state simultaneous EEG and BOLD measurements were acquired during deep sevoflurane anesthesia with burst suppression EEG in nineteen healthy volunteers. Afterwards, fMRI volumes were assigned to one of the two states (burst or suppression) as defined by the EEG. Results: In the frontal, parietal and temporal lobes as well as in the basal ganglia, BOLD signal increased after burst onset in the EEG and decreased after onset of EEG suppression. In contrast, BOLD signal in the occipital lobe was anticorrelated to electrical activity. This finding was obtained consistently in a general linear model and in raw data. Conclusions: In human brains exhibiting burst suppression EEG induced by sevoflurane, the positive correlation between BOLD signal and electrical brain activity could be confirmed in most gray matter. The exceptional behavior of the occipital lobe with an anticorrelation of BOLD signal and electrical activity might be due to specific neurovascular coupling mechanisms that are pronounced in the deeply anesthetized brain.
CRIS-Team Scopus Importer:2022-11-28
Keywords: BOLD; burst suppression; EEG; neurovascular coupling; sevoflurane

Common and distinct changes of default mode and salience network in schizophrenia and major depression - Shao, Junming; Meng, Chun; Tahmasian, Masoud; Brandl, Felix; Yang, Qinli; Luo, Guangchun; Luo, Cheng; Yao, Dezhong; Gao, Lianli; Riedl, Valentin; Wohlschlaeger, Afra; Sorg, Christian (Brain Imaging and Behavior, 2018)
Brain imaging reveals schizophrenia as a disorder of macroscopic brain networks. In particular, default mode and salience network (DMN, SN) show highly consistent alterations in both interacting brain activity and underlying brain structure. However, the same networks are also altered in major depression. This overlap in network alterations induces the question whether DMN and SN changes are different across both disorders, potentially indicating distinct underlying pathophysiological mechanisms. To address this question, we acquired T1-weighted, diffusion-weighted, and resting-state functional MRI in patients with schizophrenia, patients with major depression, and healthy controls. We measured regional gray matter volume, inter-regional structural and intrinsic functional connectivity of DMN and SN, and compared these measures across groups by generalized Wilcoxon rank tests, while controlling for symptoms and medication. When comparing patients with controls, we found in each patient group SN volume loss, impaired DMN structural connectivity, and aberrant DMN and SN functional connectivity. When comparing patient groups, SN gray matter volume loss and DMN structural connectivity reduction did not differ between groups, but in schizophrenic patients, functional hyperconnectivity between DMN and SN was less in comparison to depressed patients. Results provide evidence for distinct functional hyperconnectivity between DMN and SN in schizophrenia and major depression, while structural changes in DMN and SN were similar. Distinct hyperconnectivity suggests different pathophysiological mechanism underlying aberrant DMN-SN interactions in schizophrenia and depression.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Default mode network; Depression; Diffusion tensor imaging; Functional MRI; Salience network; Schizophrenia

Concept of the Munich/Augsburg Consortium Precision in Mental Health for the German Center of Mental Health - Falkai, Peter; Koutsouleris, Nikolaos; Bertsch, Katja; Bialas, Mirko; Binder, Elisabeth; Buehner, Markus; Buyx, Alena; Cai, Na; Cappello, Silvia; Ehring, Thomas; Gensichen, Jochen; Hamann, Johannes; et al. (Frontiers in Psychiatry, 2022)
The Federal Ministry of Education and Research (BMBF) issued a call for a new nationwide research network on mental disorders, the German Center of Mental Health (DZPG). The Munich/Augsburg consortium was selected to participate as one of six partner sites with its concept “Precision in Mental Health (PriMe): Understanding, predicting, and preventing chronicity.” PriMe bundles interdisciplinary research from the Ludwig-Maximilians-University (LMU), Technical University of Munich (TUM), University of Augsburg (UniA), Helmholtz Center Munich (HMGU), and Max Planck Institute of Psychiatry (MPIP) and has a focus on schizophrenia (SZ), bipolar disorder (BPD), and major depressive disorder (MDD). PriMe takes a longitudinal perspective on these three disorders from the at-risk stage to the first-episode, relapsing, and chronic stages. These disorders pose a major health burden because in up to 50% of patients they cause untreatable residual symptoms, which lead to early social and vocational disability, comorbidities, and excess mortality. PriMe aims at reducing mortality on different levels, e.g., reducing death by psychiatric and somatic comorbidities, and will approach this goal by addressing interdisciplinary and cross-sector approaches across the lifespan. PriMe aims to add a precision medicine framework to the DZPG that will propel deeper understanding, more accurate prediction, and personalized prevention to prevent disease chronicity and mortality across mental illnesses. This framework is structured along the translational chain and will be used by PriMe to innovate the preventive and therapeutic management of SZ, BPD, and MDD from rural to urban areas and from patients in early disease stages to patients with long-term disease courses. Research will build on platforms that include one on model systems, one on the identification and validation of predictive markers, one on the development of novel multimodal treatments, one on the regulation and strengthening of the uptake and dissemination of personalized treatments, and finally one on testing of the clinical effectiveness, utility, and scalability of such personalized treatments. In accordance with the translational chain, PriMe’s expertise includes the ability to integrate understanding of bio-behavioral processes based on innovative models, to translate this knowledge into clinical practice and to promote user participation in mental health research and care.
CRIS-Team Scopus Importer:2022-11-28
Keywords: bipolar disorder; comorbidities; depression; mortality; precision medicine; schizophrenia

Corrigendum to 'Repeated pain induces adaptations of intrinsic brain activity to reflect past and predict future pain' [NeuroImage 57/1 (2011) 206-213] - Riedl, Valentin; Valet, Michael; Woeller, Andreas; Sorg, Christian; Vogel, Dominik; Sprenger, Till; Boecker, Henning; Wohlschlaeger, Afra M.; Toelle, Thomas R. (NeuroImage, 2012)
CRIS-Team Scopus Importer:2022-11-28

Disconnection of frontal and parietal areas contributes to impaired attention in very early Alzheimer's disease - Neufang, Susanne; Akhrif, Atae; Riedl, Valentin; Foerstl, Hans; Kurz, Alexander; Zimmer, Claus; Sorg, Christian; Wohlschlaeger, Afra M. (Journal of Alzheimer's Disease, 2011)
In Alzheimer's disease (AD), the loss of cerebral connectivity has been evidenced by numerous studies. There is growing evidence of attention related failures already in prodromal stages of AD; however, connectivity changes within attention networks have been rarely reported. Here we focused on effective connectivity of top-down attention control in patients with prodromal Alzheimer's disease (pAD). We scanned 15 pAD patients and 16 healthy elderly using the Attentional Network Task and determined effective connectivity within a cingulo-fronto-parietal network using Dynamic Causal Modeling. We related connectivity parameters to structural and behavioral parameters (gray matter volume as well as reaction time) to examine the relation between affected domains. Our analyses revealed that effective connectivity from the right middle frontal gyrus to the left superior parietal cortex as well as from the right to the left superior parietal gyrus was reduced in pAD patients. Furthermore, we found that, effective connectivity varied as a function of GM volume in the patient group: right middle frontal gray matter volume significantly correlated with connectivity from the right parietal cortex to the right middle frontal gyrus as well as from the middle frontal gyrus to the anterior cingulate cortex. In addition, inter-parietal connectivity was correlated to right and left parietal gray matter volume. We conclude that, at very early stages of AD, the reduction of effective connectivity in fronto-parietal circuits is related to regional gray matter volume and contributes to impairments in top-down attentional control. © 2011 - IOS Press and the authors. All rights reserved.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Effective connectivity; prodromal Alzheimer's disease; regional gray matter volume; top down attentional control

Disrupted intrinsic networks link amyloid-β pathology and impaired cognition in prodromal Alzheimer's disease - Koch, Kathrin; Myers, Nicholas E.; Goettler, Jens; Pasquini, Lorenzo; Grimmer, Timo; Foerster, Stefan; Manoliu, Andrei; Neitzel, Julia; Kurz, Alexander; Foerstl, Hans; Riedl, Valentin; Wohlschlaeger, Afra M.; et al. (Cerebral Cortex, 2015)
Amyloid-β pathology (Aβ) and impaired cognition characterize Alzheimer's disease (AD); however, neural mechanisms that link Aβ-pathology with impaired cognition are incompletely understood. Large-scale intrinsic connectivity networks (ICNs) are potential candidates for this link: Aβ-pathology affects specific networks in early AD, these networks show disrupted connectivity, and they process specific cognitive functions impaired in AD, like memory or attention. We hypothesized that, in AD, regional changes of ICNs, which persist across rest-and cognitive task-states, might link Aβ-pathology with impaired cognition via impaired intrinsic connectivity. Pittsburgh compound B (PiB)-positron emission tomography reflecting in vivo Aβ-pathology, resting-state fMRI, task-fMRI, and cognitive testing were used in patients with prodromal AD and healthy controls. In patients, default mode network's (DMN) functional connectivity (FC) was reduced in the medial parietal cortex during rest relative to healthy controls, relatively increased in the same region during an attention-demanding task, and associated with patients' cognitive impairment. Local PiB-uptake correlated negatively with DMN connectivity. Importantly, corresponding results were found for the right lateral parietal region of an attentional network. Finally, structural equation modeling confirmed a direct influence of DMN resting-state FC on the association between Aβ-pathology and cognitive impairment. Data provide evidence that disrupted intrinsic network connectivity links Aβ-pathology with cognitive impairment in early AD.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Amyloid plaques; Impaired cognition; Intrinsic connectivity networks; PiB-PET; Prodromal Alzheimer's disease; resting-state fMRI; Task-fMRI

Effective connectivity in the default mode network is distinctively disrupted in Alzheimer's disease—A simultaneous resting-state FDG-PET/fMRI study - Scherr, Martin; Utz, Lukas; Tahmasian, Masoud; Pasquini, Lorenzo; Grothe, Michel J.; Rauschecker, Josef P.; Grimmer, Timo; Drzezga, Alexander; Sorg, Christian; Riedl, Valentin (Human Brain Mapping, 2021)
A prominent finding of postmortem and molecular imaging studies on Alzheimer's disease (AD) is the accumulation of neuropathological proteins in brain regions of the default mode network (DMN). Molecular models suggest that the progression of disease proteins depends on the directionality of signaling pathways. At network level, effective connectivity (EC) reflects directionality of signaling pathways. We hypothesized a specific pattern of EC in the DMN of patients with AD, related to cognitive impairment. Metabolic connectivity mapping is a novel measure of EC identifying regions of signaling input based on neuroenergetics. We simultaneously acquired resting-state functional MRI and FDG-PET data from patients with early AD (n = 35) and healthy subjects (n = 18) on an integrated PET/MR scanner. We identified two distinct subnetworks of EC in the DMN of healthy subjects: an anterior part with bidirectional EC between hippocampus and medial prefrontal cortex and a posterior part with predominant input into medial parietal cortex. Patients had reduced input into the medial parietal system and absent input from hippocampus into medial prefrontal cortex (p < 0.05, corrected). In a multiple linear regression with unimodal imaging and EC measures (F4,25 = 5.63, p = 0.002, r2 = 0.47), we found that EC (β = 0.45, p = 0.012) was stronger associated with cognitive deficits in patients than any of the PET and fMRI measures alone. Our approach indicates specific disruptions of EC in the DMN of patients with AD and might be suitable to test molecular theories about downstream and upstream spreading of neuropathology in AD.
CRIS-Team Scopus Importer:2022-11-28
Keywords: default mode network; directional signaling; effective connectivity; energy metabolism; resting state; simultaneous PET/fMRI

Evaluation of multiband EPI acquisitions for resting state fMRI - Preibisch, Christine; Castrillon G, J. Gabriel; Buehrer, Martin; Riedl, Valentin (PLoS ONE, 2015)
Functional magnetic resonance imaging (fMRI) and particularly resting state fMRI (rs-fMRI) is widely used to investigate resting state brain networks (RSNs) on the systems level. Echo planar imaging (EPI) is the state-of-the-art imaging technique for most fMRI studies. Therefore, improvements of EPI might lead to increased sensitivity for a large amount of studies performed every day. A number of developments to shorten acquisition time have been recently proposed and the multiband technique, allowing the simultaneous acquisition of multiple slices yielding an equivalent reduction of measurement time, is the most promising among them. While the prospect to significantly reduce acquisition time by means of high multiband acceleration factors (M) appears tempting, signal quality parameters and the sensitivity to detect common RSNs with increasing M-factor have only been partially investigated up to now. In this study, we therefore acquired rs-fMRI data from 20 healthy volunteers to systematically investigate signal characteristics and sensitivity for brain network activity in datasets with increasing M-factor, M = 2 - 4. Combined with an inplane, sensitivity encoding (SENSE), acceleration factor, S = 2, we applied a maximal acceleration factor of 8 (S2×M4). Our results suggest that an M-factor of 2 (total acceleration of 4) only causes negligible SNR decrease but reveals common RSN with increased sensitivity and stability. Further M-factor increase produced random artifacts as revealed by signal quality measures that may affect interpretation of RSNs under common scanning conditions. Given appropriate hardware, a mb-EPI sequence with a total acceleration of 4 significantly reduces overall scanning time and clearly increases sensitivity to detect common RSNs. Together, our results suggest mb-EPI at moderate acceleration factors as a novel standard for fMRI that might increase our understanding of network dynamics in healthy and diseased brains.
CRIS-Team Scopus Importer:2022-11-28

Homogeneity-based feature extraction for classification of early-stage Alzheimer's disease from functional magnetic resonance images - Plant, Claudia; Sorg, Christian; Riedl, Valentin; Wohlschläger, Afra (Proceedings of the ACM SIGKDD International Conference on Knowledge Discovery and Data Mining, 2011)
Alzheimer's disease is the most common form of age-related dementia. Early-stage diagnosis of Alzheimer is of major importance for the following reasons: Also easily curable conditions like depression, poor nutrition and drug side effects may cause symptoms like early-stage Alzheimer. Moreover, recently some medications have been developed which successfully attenuate the symptoms and delay the progression of Alzheimer, but to be effective, they need to be applied as soon as possible. However, early-stage diagnosis of Alzheimer is very difficult since the symptoms are very mild and can easily be confounded with effects of normal aging. In this paper, we introduce a bootstrapping-based feature extraction technique to identify early-stage Alzheimer's disease from resting-state functional resonance images. Our experiments demonstrate that subjects with early-stage Alzheimer's disease can be distinguished with an accuracy of 79% from age-matched healthy subjects using a support vector machine on the extracted features. © 2011 ACM.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Algorithms

How do you make me feel better? Social cognitive emotion regulation and the default mode network - Xie, Xiyao; Bratec, Satja Mulej; Schmid, Gabriele; Meng, Chun; Doll, Anselm; Wohlschlaeger, Afra; Finke, Kathrin; Foestl, Hans; Zimmer, Claus; Pekrun, Reinhard; Schilbach, Leonhard; Riedl, Valentin; et al. (NeuroImage, 2016)
Socially-induced cognitive emotion regulation (Social-Reg) is crucial for emotional well-being and social functioning; however, its brain mechanisms remain poorly understood. Given that both social cognition and cognitive emotion regulation engage key regions of the default-mode network (DMN), we hypothesized that Social-Reg would rely on the DMN, and that its effectiveness would be associated with social functioning. During functional MRI, negative emotions were elicited by pictures, and - via short instructions - a psychotherapist either down-regulated participants' emotions by employing reappraisal (Reg), or asked them to simply look at the pictures (Look). Adult Attachment Scale was used to measure social functioning. Contrasting Reg versus Look, aversive emotions were successfully reduced during Social-Reg, with increased activations in the prefrontal and parietal cortices, precuneus and the left temporo-parietal junction. These activations covered key nodes of the DMN and were associated with Social-Reg success. Furthermore, participants' attachment security was positively correlated with both Social-Reg success and orbitofrontal cortex involvement during Social-Reg. In addition, specificity of the neural correlates of Social-Reg was confirmed by comparisons with participants' DMN activity at rest and their brain activations during a typical emotional self-regulation task based on the same experimental paradigm without a psychotherapist. Our results provide first evidence for the specific involvement of the DMN in Social-Reg, and the association of Social-Reg with individual differences in attachment security. The findings suggest that DMN dysfunction, found in many neuropsychiatric disorders, may impair the ability to benefit from Social-Reg.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Attachment security; Cognitive emotion regulation; Default mode network; Social default mode network; Social emotion regulation; Socially-induced cognitive emotion regulation

Imbalance in subregional connectivity of the right temporoparietal junction in major depression - Poeppl, Timm B.; Mueller, Veronika I.; Hoffstaedter, Felix; Bzdok, Danilo; Laird, Angela R.; Fox, Peter T.; Langguth, Berthold; Rupprecht, Rainer; Sorg, Christian; Riedl, Valentin; Goya-Maldonado, Roberto; Gruber, Oliver; et al. (Human Brain Mapping, 2016)
Major depressive disorder (MDD) involves impairment in cognitive and interpersonal functioning. The right temporoparietal junction (RTPJ) is a key brain region subserving cognitive-attentional and social processes. Yet, findings on the involvement of the RTPJ in the pathophysiology of MDD have so far been controversial. Recent connectivity-based parcellation data revealed a topofunctional dualism within the RTPJ, linking its anterior and posterior part (aRTPJ/pRTPJ) to antagonistic brain networks for attentional and social processing, respectively. Comparing functional resting-state connectivity of the aRTPJ and pRTPJ in 72 MDD patients and 76 well-matched healthy controls, we found a seed (aRTPJ/pRTPJ) × diagnosis (MDD/controls) interaction in functional connectivity for eight regions. Employing meta-data from a large-scale neuroimaging database, functional characterization of these regions exhibiting differentially altered connectivity with the aRTPJ/pRTPJ revealed associations with cognitive (dorsolateral prefrontal cortex, parahippocampus) and behavioral (posterior medial frontal cortex) control, visuospatial processing (dorsal visual cortex), reward (subgenual anterior cingulate cortex, medial orbitofrontal cortex, posterior cingulate cortex), as well as memory retrieval and social cognition (precuneus). These findings suggest that an imbalance in connectivity of subregions, rather than disturbed connectivity of the RTPJ as a whole, characterizes the connectional disruption of the RTPJ in MDD. This imbalance may account for key symptoms of MDD in cognitive, emotional, and social domains. Hum Brain Mapp 37:2931–2942, 2016. © 2016 Wiley Periodicals, Inc.
CRIS-Team Scopus Importer:2022-11-28
Keywords: connectivity; depression; functional magnetic resonance imaging; major depressive disorder; resting state; right temporoparietal junction

Impact of Alzheimer's disease on the functional connectivity of spontaneous brain activity - Sorg, Christian; Riedl, Valentin; Perneczky, Robert; Kurz, Alexander; Wohlschlaeger, Afra M. (Current Alzheimer Research, 2009)
Alzheimer's disease (AD) prominently affects the structure and function of cerebral networks. Reflecting the complex network structure of the brain, spontaneous brain activity is organized by synchronized activity across distinct temporal and spatial scales. Temporal correlations of the functional MRI (fMRI) signal during rest have been used to characterize the impact of AD on the functional connectivity of spontaneous brain activity. Here we review studies using resting-state fMRI (rs-fMRI) to explore AD-induced changes of synchronized intrinsic activity at three levels of brain organization: the regional, inter-regional and large-scale level. Changes in posterior areas of the default network (DN) and the medial temporal lobes seem to be central to AD. These areas show remarkable disturbances in neuronal communication at all spatial levels and in very early stages of the disease. Finally, rs-fMRI seems to have the potential to produce connectivity-related biomarkers that distinguish AD and healthy aging. ©2009 Bentham Science Publishers Ltd.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Alzheimer's disease; fMRI; Functional connectivity; Local integration; Resting state; Resting state networks; Small world; Spontaneous brain activity

Impact of global mean normalization on regional glucose metabolism in the human brain - Mortensen, Kristian N.; Gjedde, Albert; Thompson, Garth J.; Herman, Peter; Paret, Maxime J.; Rothman, Douglas L.; Kupers, Ron; Ptito, Maurice; Stender, Johan; Laureys, Steven; Riedl, Valentin; Alkire, Michael T.; et al. (Neural Plasticity, 2018)
Because the human brain consumes a disproportionate fraction of the resting body's energy, positron emission tomography (PET) measurements of absolute glucose metabolism (CMRglc) can serve as disease biomarkers. Global mean normalization (GMN) of PET data reveals disease-based differences from healthy individuals as fractional changes across regions relative to a global mean. To assess the impact of GMN applied to metabolic data, we compared CMRglc with and without GMN in healthy awake volunteers with eyes closed (i.e., control) against specific physiological/clinical states, including healthy/awake with eyes open, healthy/awake but congenitally blind, healthy/sedated with anesthetics, and patients with disorders of consciousness. Without GMN, global CMRglc alterations compared to control were detected in all conditions except in congenitally blind where regional CMRglc variations were detected in the visual cortex. However, GMN introduced regional and bidirectional CMRglc changes at smaller fractions of the quantitative delocalized changes. While global information was lost with GMN, the quantitative approach (i.e., a validated method for quantitative baseline metabolic activity without GMN) not only preserved global CMRglc alterations induced by opening eyes, sedation, and varying consciousness but also detected regional CMRglc variations in the congenitally blind. These results caution the use of GMN upon PET-measured CMRglc data in health and disease.
CRIS-Team Scopus Importer:2022-11-28

Increased global interaction across functional brain modules during cognitive emotion regulation - Brandl, Felix; Bratec, Satja Mulej; Xie, Xiyao; Wohlschlager, Afra M.; Riedl, Valentin; Meng, Chun; Sorg, Christian (Cerebral Cortex, 2018)
Cognitive emotion regulation (CER) enables humans to flexibly modulate their emotions. While local theories of CER neurobiology suggest interactions between specialized local brain circuits underlying CER, e.g., in subparts of amygdala and medial prefrontal cortices (mPFC), global theories hypothesize global interaction increases among larger functional brain modules comprising local circuits. We tested the global CER hypothesis using graph-based whole-brain network analysis of functional MRI data during aversive emotional processing with and without CER. During CER, global between-module interaction across stable functional network modules increased. Global interaction increase was particularly driven by subregions of amygdala and cuneus—nodes of highest nodal participation—that overlapped with CER-specific local activations, and by mPFC and posterior cingulate as relevant connector hubs. Results provide evidence for the global nature of human CER, complementing functional specialization of embedded local brain circuits during successful CER.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Cognitive emotion regulation; Functional connectivity; Global interaction; Graph theory; Task fMRI

Increased Intrinsic Activity of Medial-Temporal Lobe Subregions is Associated with Decreased Cortical Thickness of Medial-Parietal Areas in Patients with Alzheimer's Disease Dementia - Pasquini, Lorenzo; Scherr, Martin; Tahmasian, Masoud; Myers, Nicholas E.; Ortner, Marion; Kurz, Alexander; Foerstl, Hans; Zimmer, Claus; Grimmer, Timo; Akhrif, Atae; Wohlschlaeger, Afra M.; Riedl, Valentin; et al. (Journal of Alzheimer's Disease, 2016)
In Alzheimer's disease (AD), disrupted connectivity between medial-parietal cortices and medial-temporal lobes (MTL) is linked with increased MTL local functional connectivity, and parietal atrophy is associated with increased MTL memory activation. We hypothesized that intrinsic activity in MTL subregions is increased and associated with medial-parietal degeneration and impaired memory in AD. To test this hypothesis, resting-state-functional and structural-MRI was assessed in 22 healthy controls, 22 mild cognitive impairment patients, and 21 AD-dementia patients. Intrinsic activity was measured by power-spectrum density of blood-oxygenation-level-dependent signal, medial-parietal degeneration by cortical thinning. In AD-dementia patients, intrinsic activity was increased for several right MTL subregions. Raised intrinsic activity in dentate gyrus and cornu ammonis 1 was associated with cortical thinning in posterior cingulate cortices, and at-trend with impaired delayed recall. Critically, increased intrinsic activity in the right entorhinal cortex was associated with ipsilateral posterior cingulate degeneration. Our results provide evidence that in AD, intrinsic activity in MTL subregions is increased and associated with medial-parietal atrophy. Results fit a model in which medial-parietal degeneration contributes to MTL dysconnectivity from medial-parietal cortices, potentially underpinning disinhibition-like changes in MTL activity.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Alzheimer's disease; atrophy; functional magnetic resonance imaging; hippocampus; medial-parietal cortex; medial-temporal lobe; neurodegeneration; neuroimaging; physiopathology; resting-state activity

Increased intrinsic brain activity in the striatum reflects symptom dimensions in schizophrenia - Sorg, Christian; Manoliu, Andrei; Neufang, Susanne; Myers, Nicholas; Peters, Henning; Schwerthoeffer, Dirk; Scherr, Martin; Muehlau, Mark; Zimmer, Claus; Drzezga, Alexander; Foerstl, Hans; Baeuml, Josef; et al. (Schizophrenia Bulletin, 2013)
Striatal dysfunction is thought to be a fundamental element in schizophrenia. Striatal dopamine dysfunction impacts on reward processing and learning and is present even at rest. Here, we addressed the question whether and how spontaneous neuronal activity in the striatum is altered in schizophrenia. We therefore assessed intrinsic striatal activity and its relation with disorder states and symptom dimensions in patients with schizophrenia. We performed resting-state functional (rs-fMRI) and structural magnetic resonance imaging as well as psychometric assessment in 21 schizophrenic patients during psychosis. On average 9 months later, we acquired follow-up data during psychotic remission and with comparable levels of antipsychotic medication. Twenty-one age-and sex-matched healthy controls were included in the study. Independent component analysis of fMRI data yielded spatial maps and time-courses of coherent ongoing blood-oxygen-level-dependent signal fluctuations, which were used for group comparisons and correlation analyses with scores of the positive and negative syndrome scale. During psychosis, coherent intrinsic activity of the striatum was increased in the dorsal part and correlated with positive symptoms such as delusion and hallucination. In psychotic remission of the same patients, activity of the ventral striatum was increased and correlated with negative symptoms such as emotional withdrawal and blunted affect. Results were controlled for volumetric and medication effects. These data provide first evidence that in schizophrenia intrinsic activity is changed in the striatum and corresponds to disorder states and symptom dimensions. © 2013 The Author.
CRIS-Team Scopus Importer:2022-11-28
Keywords: intrinsic brain activity; psychosis; resting-state fMRI; schizophrenia; striatum

Insular dysfunction within the salience network is associated with severity of symptoms and aberrant inter-network connectivity in major depressive disorder - Manoliu, Andrei; Meng, Chun; Brandl, Felix; Doll, Anselm; Tahmasian, Masoud; Scherr, Martin; Schwerthoeffer, Dirk; Zimmer, Claus; Foerstl, Hans; Baeuml, Josef; Riedl, Valentin; Wohlschlaeger, Afra M.; et al. (Frontiers in Human Neuroscience, 2014)
Major depressive disorder (MDD) is characterized by altered intrinsic functional connectivity within (intra-iFC) intrinsic connectivity networks (ICNs), such as the Default Mode- (DMN), Salience- (SN) and Central Executive Network (CEN). It has been proposed that aberrant switching between DMN-mediated self-referential and CEN-mediated goal-directed cognitive processes might contribute to MDD, possibly explaining patients' difficulties to disengage the processing of self-focused, often negatively biased thoughts. Recently, it has been shown that the right anterior insula (rAI) within the SN is modulating DMN/CEN interactions. Since structural and functional alterations within the AI have been frequently reported in MDD, we hypothesized that aberrant intra-iFC in the SN's rAI is associated with both aberrant iFC between DMN and CEN (inter-iFC) and severity of symptoms in MDD. Twenty-five patients with MDD and 25 healthy controls were assessed using resting-state fMRI (rs-fMRI) and psychometric examination. High-model-order independent component analysis (ICA) of rs-fMRI data was performed to identify ICNs including DMN, SN, and CEN. Intra-iFC within and inter-iFC between distinct subsystems of the DMN, SN, and CEN were calculated, compared between groups and correlated with the severity of symptoms. Patients with MDD showed (1) decreased intra-iFC within the SN's rAI, (2) decreased inter-iFC between the DMN and CEN, and (3) increased inter-iFC between the SN and DMN. Moreover, decreased intra-iFC in the SN's rAI was associated with severity of symptoms and aberrant DMN/CEN interactions, with the latter losing significance after correction for multiple comparisons. Our results provide evidence for a relationship between aberrant intra-iFC in the salience network's rAI, aberrant DMN/CEN interactions and severity of symptoms, suggesting a link between aberrant salience mapping, abnormal coordination of DMN/CEN based cognitive processes and psychopathology in MDD. © 2014 Manoliu, Meng, Brandl, Doll, Tahmasian, Scherr, Schwerthöffer, Zimmer, Förstl, Bäuml, Riedl, Wohlschläger and Sorg.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Anterior insula; Central executive network; Default mode network; Intrinsic functional connectivity; Intrinsic networks; Major depressive disorder; Salience network; Triple network hypothesis

Integrity of neurocognitive networks in dementing disorders as measured with simultaneous pet/functional mri - Ripp, Isabelle; Stadhouders, Thomas; Savio, Alexandre; Goldhardt, Oliver; Cabello, Jorge; Calhoun, Vince; Riedl, Valentin; Hedderich, Dennis; Diehl-Schmid, Janine; Grimmer, Timo; Yakushev, Igor (Journal of Nuclear Medicine, 2020)
Functional MRI (fMRI) studies have reported altered integrity of large-scale neurocognitive networks (NCNs) in dementing disorders. However, findings on the specificity of these alterations in patients with Alzheimer disease (AD) and behavioral-variant frontotemporal dementia (bvFTD) are still limited. Recently, NCNs have been successfully captured using PET with 18F-FDG. Methods: Network integrity was measured in 72 individuals (38 male) with mild AD or bvFTD, and in healthy controls, using a simultaneous restingstate fMRI and 18F-FDG PET. Indices of network integrity were calculated for each subject, network, and imaging modality. Results: In either modality, independent-component analysis revealed 4 major NCNs: Anterior default-mode network (DMN), posterior DMN, salience network, and right central executive network (CEN). In fMRI data, the integrity of the posterior DMN was found to be significantly reduced in both patient groups relative to controls. In the AD group the anterior DMN and CEN appeared to be additionally affected. In PET data, only the integrity of the posterior DMN in patients with AD was reduced, whereas 3 remaining networks appeared to be affected only in patients with bvFTD. In a logistic regression analysis, the integrity of the anterior DMN as measured with PET alone accurately differentiated between the patient groups. A correlation between indices of 2 imaging modalities was low overall. Conclusion: FMRI and 18F-FDG PET capture partly different aspects of network integrity. A higher disease specificity for NCNs as derived from PET data supports metabolic connectivity imaging as a promising diagnostic tool.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Alzheimer disease; Frontotemporal dementia; Multimodal neuroimaging; PET; Resting-state networks

Intrinsic brain activity of cognitively normal older persons resembles more that of patients both with and at risk for Alzheimer's disease than that of healthy younger persons - Pasquini, Lorenzo; Tonch, Annika; Plant, Claudia; Zherdin, Andrew; Ortner, Marion; Kurz, Alexander; Förstl, Hans; Zimmer, Claus; Grimmer, Timo; Wohlschäger, Afra; Riedl, Valentin; Sorg, Christian (Brain Connectivity, 2014)
In Alzheimer's disease (AD), recent findings suggest that amyloid-β (Aβ)-pathology might start 20-30 years before first cognitive symptoms arise. To account for age as most relevant risk factor for sporadic AD, it has been hypothesized that lifespan intrinsic (i.e., ongoing) activity of hetero-modal brain areas with highest levels of functional connectivity triggers Aβ-pathology. This model induces the simple question whether in older persons without any cognitive symptoms intrinsic activity of hetero-modal areas is more similar to that of symptomatic patients with AD or to that of younger healthy persons. We hypothesize that due to advanced age and therefore potential impact of pre-clinical AD, intrinsic activity of older persons resembles more that of patients than that of younger controls. We tested this hypothesis in younger (ca. 25 years) and older healthy persons (ca. 70 years) and patients with mild cognitive impairment and AD-dementia (ca. 70 years) by the use of resting-state functional magnetic resonance imaging, distinct measures of intrinsic brain activity, and different hierarchical clustering approaches. Independently of applied methods and involved areas, healthy older persons' intrinsic brain activity was consistently more alike that of patients than that of younger controls. Our result provides evidence for larger similarity in intrinsic brain activity between healthy older persons and patients with or at-risk for AD than between older and younger ones, suggesting a significant proportion of pre-clinical AD cases in the group of cognitively normal older people. The observed link of aging and AD with intrinsic brain activity supports the view that lifespan intrinsic activity may contribute critically to the pathogenesis of AD.
CRIS-Team Scopus Importer:2022-11-28
Keywords: aging; Alzheimer's disease; functional connectivity; hierarchical clustering; intrinsic brain activity; mild cognitive impairment; resting-state functional MRI

Intrinsic network connectivity reflects consistency of synesthetic experiences - Dovern, Anna; Fink, Gereon R.; Fromme, A. Christina B.; Wohlschlaeger, Afra M.; Weiss, Peter H.; Riedl, Valentin (Journal of Neuroscience, 2012)
Studying cognitive processes underlying synesthesia, a condition in which stimulation of one sensory modality automatically leads to abnormal additional sensory perception, allows insights into the neural mechanisms of normal and abnormal cross-modal sensory processing. Consistent with the notion that synesthesia results from hyperconnectivity, functional connectivity analysis (adopting independent component analysis and seed-based correlation analysis) of resting-state functional magnetic resonance imaging data of 12 grapheme- color synesthetes and 12 nonsynesthetic control subjects revealed, in addition to increased intranetwork connectivity, both a global and a specific (medial and lateral visual networks to a right frontoparietal network) increase of intrinsic internetwork connectivity in grapheme- color synesthesia. Moreover, this increased intrinsic network connectivity reflected the strength of synesthetic experiences. These findings constitute the first direct evidence of increased functional network connectivity in synesthesia. In addition to this significant contribution to the understanding of the neural mechanisms of synesthesia, our results have important general implications. In combination with data derived from clinical populations, our data strongly suggest that altered differences in intrinsic network connectivity are directly related to the phenomenology of human experiences. © 2012 the authors.
CRIS-Team Scopus Importer:2022-11-28

Joint Multi-modal Parcellation of the Human Striatum: Functions and Clinical Relevance - Liu, Xiaojin; Eickhoff, Simon B.; Hoffstaedter, Felix; Genon, Sarah; Caspers, Svenja; Reetz, Kathrin; Dogan, Imis; Eickhoff, Claudia R.; Chen, Ji; Caspers, Julian; Reuter, Niels; Mathys, Christian; et al. (Neuroscience Bulletin, 2020)
The human striatum is essential for both low- and high-level functions and has been implicated in the pathophysiology of various prevalent disorders, including Parkinson’s disease (PD) and schizophrenia (SCZ). It is known to consist of structurally and functionally divergent subdivisions. However, previous parcellations are based on a single neuroimaging modality, leaving the extent of the multi-modal organization of the striatum unknown. Here, we investigated the organization of the striatum across three modalities—resting-state functional connectivity, probabilistic diffusion tractography, and structural covariance—to provide a holistic convergent view of its structure and function. We found convergent clusters in the dorsal, dorsolateral, rostral, ventral, and caudal striatum. Functional characterization revealed the anterior striatum to be mainly associated with cognitive and emotional functions, while the caudal striatum was related to action execution. Interestingly, significant structural atrophy in the rostral and ventral striatum was common to both PD and SCZ, but atrophy in the dorsolateral striatum was specifically attributable to PD. Our study revealed a cross-modal convergent organization of the striatum, representing a fundamental topographical model that can be useful for investigating structural and functional variability in aging and in clinical conditions.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Connectivity-based parcellation; Convergent clusters; Multi-modal; Parkinson’s disease; Schizophrenia; Striatum; Voxel-based morphometry

Link between hippocampus' raised local and eased global intrinsic connectivity in AD - Pasquini, Lorenzo; Scherr, Martin; Tahmasian, Masoud; Meng, Chun; Myers, Nicholas E.; Ortner, Marion; Muehlau, Mark; Kurz, Alexander; Foerstl, Hans; Zimmer, Claus; Grimmer, Timo; Wohlschlaeger, Afra M.; et al. (Alzheimers & Dementia, 2015)
Background The hippocampus (HP) is part of the default mode network (DMN), and both are key targets of Alzheimer's disease (AD). Because of widespread network degeneration, it has been suggested that increasing HP disconnection from the DMN may lead to progressive disinhibition of intra-HP synchronized activity. Methods To analyze HP local (i.e., within HP) and global (i.e., within DMN) intrinsic functional connectivity (local/global intrinsic functional connectivity [iFC]), healthy controls and patients with mild cognitive impairment and AD dementia were assessed by spatial high and normal resolution resting-state functional magnetic resonance imaging. Results Although patients' parietal local-iFC was reduced and positively correlated with reduced global-iFC within the DMN, HP local connectivity was progressively increased and negatively correlated with HP decreased global connectivity. Increased intra-HP connectivity was associated with impaired memory. Conclusion Our result demonstrates a link between increased local and reduced global hippocampal connectivity in AD. Increased intra-HP synchrony may contribute to distinct symptoms such as memory impairment or more speculatively epileptic seizure.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Alzheimer's disease; Default mode network; High-resolution resting-state fMRI; Hippocampus; Independent component analysis; Intrinsic functional connectivity; Mild cognitive impairment; Synchrony

Local activity determines functional connectivity in the resting human brain: A simultaneous FDG-PET/fMRI study - Riedl, Valentin; Bienkowska, Katarzyna; Strobel, Carola; Tahmasian, Masoud; Grimmer, Timo; Foerster, Stefan; Friston, Karl J.; Sorg, Christian; Drzezga, Alexander (Journal of Neuroscience, 2014)
Over the last decade, synchronized resting-state fluctuations of blood oxygenation level-dependent (BOLD) signals between remote brain areas [so-called BOLD resting-state functional connectivity (rs-FC)] have gained enormous relevance in systems and clinical neuroscience. However, the neural underpinnings of rs-FC are still incompletely understood. Using simultaneous positron emission tomography/magnetic resonance imaging we here directly investigated the relationship between rs-FC and local neuronal activity in humans. Computational models suggest a mechanistic link between the dynamics of local neuronal activity and the functional coupling among distributed brain regions. Therefore, we hypothesized that the local activity (LA) of a region at rest determines its rs-FC. To test this hypothesis, we simultaneously measured both LA (glucose metabolism) and rs-FC (via synchronized BOLD fluctuations) during conditions of eyes closed or eyes open. During eyes open, LA increased in the visual system, and the salience network (i.e., cingulate and insular cortices) and the pattern of elevated LA coincided almost exactly with the spatial pattern of increased rs-FC. Specifically, the voxelwise regional profile of LA in these areas strongly correlated with the regional pattern of rs-FC among the same regions (e.g., LA in primary visual cortex accounts for 50%, and LA in anterior cingulate accounts for 20% of rs-FC with the visual system). These data provide the first direct evidence in humans that local neuronal activity determines BOLD FC at rest. Beyond its relevance for the neuronal basis of coherent BOLD signal fluctuations, our procedure may translate into clinical research particularly to investigate potentially aberrant links between local dynamics and remote functional coupling in patients with neuropsychiatric disorders. © 2014 the authors.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Energy metabolism; Functional connectivity; PET/MR imaging

Medial prefrontal aberrations in major depressive disorder revealed by cytoarchitectonically informed voxel-based morphometry - Bludau, Sebastian; Bzdok, Danilo; Gruber, Oliver; Kohn, Nils; Riedl, Valentin; Sorg, Christian; Palomero-Gallagher, Nicola; Mueller, Veronika I.; Hoffstaedter, Felix; Amunts, Katrin; Eickhoff, Simon B. (American Journal of Psychiatry, 2016)
Objective: The heterogeneous human frontal pole has been identified as a node in the dysfunctional network of major depressive disorder. The contribution of the medial (socioaffective) versus lateral (cognitive) frontal pole to major depression pathogenesis is currently unclear. The authors performed morphometric comparison of the microstructurally informed subdivisions of human frontal pole between depressed patients and comparison subjects using both uni- and multivariate statistics. Method: Multisite voxel- and region-based morphometric MRI analysis was conducted in 73 depressed patients and 73 matched comparison subjects without psychiatric history. Frontal pole volume was first compared between depressed patients and comparison subjects by subdivision-wise classical morphometric analysis. In a second approach, frontal pole volume was compared by subdivision-naive multivariate searchlight analysis based on support vector machines. Results: Subdivision-wise morphometric analysis found a significantly smaller medial frontal pole in depressed patients, with a negative correlation of disease severity and duration. Histologically uninformed multivariate voxel-wise statistics provided converging evidence for structural aberrations specific to the microstructurally defined medial area of the frontal pole in depressed patients. Conclusions: Across disparatemethods, subregion specificity in the leftmedial frontalpole volume in depressed patients was demonstrated. Indeed, the frontal pole was shown to structurally and functionally connect to other key regions in major depression pathology, such as the anterior cingulate cortex and the amygdala via the uncinate fasciculus. Present and previous findings consolidate the left medial portion of the frontal pole as particularly altered in major depression.
CRIS-Team Scopus Importer:2022-11-28

Metabolic connectivity mapping reveals effective connectivity in the resting human brain - Riedl, Valentin; Utz, Lukas; Castrillon, Gabriel; Grimmer, Timo; Rauschecker, Josef P.; Ploner, Markus; Friston, Karl J.; Drzezga, Alexander; Sorg, Christian (Proceedings of the National Academy of Sciences of the United States of America, 2016)
Directionality of signaling among brain regions provides essential information about human cognition and disease states. Assessing such effective connectivity (EC) across brain states using functional magnetic resonance imaging (fMRI) alone has proven difficult, however. We propose a novel measure of EC, termed metabolic connectivity mapping (MCM), that integrates undirected functional connectivity (FC) with local energy metabolism from fMRI and positron emission tomography (PET) data acquired simultaneously. This method is based on the concept that most energy required for neuronal communication is consumed postsynaptically, i.e., at the target neurons. We investigated MCM and possible changes in EC within the physiological range using "eyes open" versus "eyes closed" conditions in healthy subjects. Independent of condition, MCM reliably detected stable and bidirectional communication between early and higher visual regions. Moreover, we found stable top-down signaling from a frontoparietal network including frontal eye fields. In contrast, we found additional top-down signaling from all major clusters of the salience network to early visual cortex only in the eyes open condition. MCM revealed consistent bidirectional and unidirectional signaling across the entire cortex, along with prominent changes in network interactions across two simple brain states. We propose MCM as a novel approach for inferring EC from neuronal energy metabolism that is ideally suited to study signaling hierarchies in the brain and their defects in brain disorders.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Directional signaling; Effective connectivity; Energy metabolism; Resting state; Simultaneous PET/fMRI

More consistently altered connectivity patterns for cerebellum and medial temporal lobes than for amygdala and striatum in schizophrenia - Peters, Henning; Shao, Junming; Scherr, Martin; Schwerthoeffer, Dirk; Zimmer, Claus; Foerstl, Hans; Baeuml, Josef; Wohlschlaeger, Afra; Riedl, Valentin; Koch, Kathrin; Sorg, Christian (Frontiers in Human Neuroscience, 2016)
Background: Brain architecture can be divided into a cortico-thalamic system and modulatory “subcortical-cerebellar” systems containing key structures such as striatum, medial temporal lobes (MTLs), amygdala, and cerebellum. Subcortical-cerebellar systems are known to be altered in schizophrenia. In particular, intrinsic functional brain connectivity (iFC) between these systems has been consistently demonstrated in patients. While altered connectivity is known for each subcortical-cerebellar system separately, it is unknown whether subcortical-cerebellar systems' connectivity patterns with the cortico-thalamic system are comparably altered across systems, i.e. if separate subcortical-cerebellar systems' connectivity patterns are consistent across patients. Methods: To investigate this question, 18 patients with schizophrenia (3 unmedicated, 15 medicated with atypical antipsychotics) and 18 healthy controls were assessed by resting-state functional magnetic resonance imaging (fMRI). Independent component analysis of fMRI data revealed cortical intrinsic brain networks (NWs) with time courses representing proxies for cortico-thalamic system activity. Subcortical-cerebellar systems' activity was represented by fMRI-based time courses of selected regions-of-interest (ROIs; i.e. striatum, MTL, amygdala, cerebellum). Correlation analysis among ROI-and NWs-time courses yielded individual connectivity matrices [i.e. connectivity between NW and ROIs (allROIs-NW, separateROI-NW), only NWs (NWs-NWs), and only ROIs (allROIs-allROIs)] as main outcome measures, which were classified by support-vector-machine-based (SVM) leave-one-out cross-validation. Differences in classification accuracy were statistically evaluated for consistency across subjects and systems. Results: Correlation matrices based on allROIs-NWs yielded 91% classification accuracy, which was significantly superior to allROIs-allROIs and NWs-NWs (56 and 74%, respectively). Considering separate subcortical-cerebellar systems, cerebellum-NWs and MTL-NWs reached highest accuracy values with 91 and 85%, respectively, while those of striatum-NW and amygdala-NW were significantly lower with about 65% classification accuracy. Conclusion: Results provide initial evidence for differential consistency of altered intrinsic connectivity patterns between subcortical-cerebellar systems and the corticothalamic system. Data suggest that differential dysconnectivity patterns between subcortical-cerebellar and cortical systems might reflect different disease states or patient subgroups.
CRIS-Team Scopus Importer:2022-11-28
Keywords: FMRI; Functional connectivity (FC); Multivariate pattern analysis; Schizophrenia; Subcortical; Support vector machine

Neural Correlates of Sevoflurane-induced Unconsciousness Identified by Simultaneous Functional Magnetic Resonance Imaging and Electroencephalography - Ranft, Andreas; Golkowski, Daniel; Kiel, Tobias; Riedl, Valentin; Kohl, Philipp; Rohrer, Guido; Pientka, Joachim; Berger, Sebastian; Thul, Alexander; Maurer, Max; Preibisch, Christine; Zimmer, Claus; et al. (Anesthesiology, 2016)
Background: The neural correlates of anesthetic-induced unconsciousness have yet to be fully elucidated. Sedative and anesthetic states induced by propofol have been studied extensively, consistently revealing a decrease of frontoparietal and thalamocortical connectivity. There is, however, less understanding of the effects of halogenated ethers on functional brain networks. Methods: The authors recorded simultaneous resting-state functional magnetic resonance imaging and electroencephalography in 16 artificially ventilated volunteers during sevoflurane anesthesia at burst suppression and 3 and 2 vol% steady-state concentrations for 700 s each to assess functional connectivity changes compared to wakefulness. Electroencephalographic data were analyzed using symbolic transfer entropy (surrogate of information transfer) and permutation entropy (surrogate of cortical information processing). Functional magnetic resonance imaging data were analyzed by an independent component analysis and a region-of-interest-based analysis. Results: Electroencephalographic analysis showed a significant reduction of anterior-to-posterior symbolic transfer entropy and global permutation entropy. At 2 vol% sevoflurane concentrations, frontal and thalamic networks identified by independent component analysis showed significantly reduced within-network connectivity. Primary sensory networks did not show a significant change. At burst suppression, all cortical networks showed significantly reduced functional connectivity. Region-of-interest-based thalamic connectivity at 2 vol% was significantly reduced to frontoparietal and posterior cingulate cortices but not to sensory areas. Conclusions: Sevoflurane decreased frontal and thalamocortical connectivity. The changes in blood oxygenation level dependent connectivity were consistent with reduced anterior-to-posterior directed connectivity and reduced cortical information processing. These data advance the understanding of sevoflurane-induced unconsciousness and contribute to a neural basis of electroencephalographic measures that hold promise for intraoperative anesthesia monitoring.
CRIS-Team Scopus Importer:2022-11-28

Neurobiological Divergence of the Positive and Negative Schizophrenia Subtypes Identified on a New Factor Structure of Psychopathology Using Non-negative Factorization: An International Machine Learning Study - Chen, Ji; Patil, Kaustubh R.; Weis, Susanne; Sim, Kang; Nickl-Jockschat, Thomas; Zhou, Juan; Aleman, Andre; Sommer, Iris E.; Liemburg, Edith J.; Hoffstaedter, Felix; Habel, Ute; Derntl, Birgit; et al. (Biological Psychiatry, 2020)
Background: Disentangling psychopathological heterogeneity in schizophrenia is challenging, and previous results remain inconclusive. We employed advanced machine learning to identify a stable and generalizable factorization of the Positive and Negative Syndrome Scale and used it to identify psychopathological subtypes as well as their neurobiological differentiations. Methods: Positive and Negative Syndrome Scale data from the Pharmacotherapy Monitoring and Outcome Survey cohort (1545 patients; 586 followed up after 1.35 ± 0.70 years) were used for learning the factor structure by an orthonormal projective non-negative factorization. An international sample, pooled from 9 medical centers across Europe, the United States, and Asia (490 patients), was used for validation. Patients were clustered into psychopathological subtypes based on the identified factor structure, and the neurobiological divergence between the subtypes was assessed by classification analysis on functional magnetic resonance imaging connectivity patterns. Results: A 4-factor structure representing negative, positive, affective, and cognitive symptoms was identified as the most stable and generalizable representation of psychopathology. It showed higher internal consistency than the original Positive and Negative Syndrome Scale subscales and previously proposed factor models. Based on this representation, the positive–negative dichotomy was confirmed as the (only) robust psychopathological subtypes, and these subtypes were longitudinally stable in about 80% of the repeatedly assessed patients. Finally, the individual subtype could be predicted with good accuracy from functional connectivity profiles of the ventromedial frontal cortex, temporoparietal junction, and precuneus. Conclusions: Machine learning applied to multisite data with cross-validation yielded a factorization generalizable across populations and medical systems. Together with subtyping and the demonstrated ability to predict subtype membership from neuroimaging data, this work further disentangles the heterogeneity in schizophrenia.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Brain imaging; Machine learning; Multivariate classification; Non-negative factorization; Schizophrenia; Subtyping

Ongoing slow fluctuations in V1 impact on visual perception - Wohlschlaeger, Afra M.; Glim, Sarah; Shao, Junming; Draheim, Johanna; Koehler, Lina; Lourenco, Susana; Riedl, Valentin; Sorg, Christian (Frontiers in Human Neuroscience, 2016)
The human brain’s ongoing activity is characterized by intrinsic networks of coherent fluctuations, measured for example with correlated functional magnetic resonance imaging signals. So far, however, the brain processes underlying this ongoing blood oxygenation level dependent (BOLD) signal orchestration and their direct relevance for human behavior are not sufficiently understood. In this study, we address the question of whether and how ongoing BOLD activity within intrinsic occipital networks impacts on conscious visual perception. To this end, backwardly masked targets were presented in participants’ left visual field only, leaving the ipsi-lateral occipital areas entirely free from direct effects of task throughout the experiment. Signal time courses of ipsi-lateral BOLD fluctuations in visual areas V1 and V2 were then used as proxies for the ongoing contra-lateral BOLD activity within the bilateral networks. Magnitude and phase of these fluctuations were compared in trials with and without conscious visual perception, operationalized by means of subjective confidence ratings. Our results show that ipsi-lateral BOLD magnitudes in V1 were significantly higher at times of peak response when the target was perceived consciously. A significant difference between conscious and non-conscious perception with regard to the pre-target phase of an intrinsic-frequency regime suggests that ongoing V1 fluctuations exert a decisive impact on the access to consciousness already before stimulation. Both effects were absent in V2. These results thus support the notion that ongoing slow BOLD activity within intrinsic networks covering V1 represents localized processes that modulate the degree of readiness for the emergence of visual consciousness.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Backward masking; Ongoing BOLD signal; Pre-stimulus activity; Slow fluctuations; Visual consciousness

Opposite dynamics of GABA and glutamate levels in the occipital cortex during visual processing - Kurcyus, Katarzyna; Annac, Efsun; Hanning, Nina M.; Harris, Ashley D.; Oeltzschner, Georg; Edden, Richard; Riedl, Valentin (Journal of Neuroscience, 2018)
Magnetic resonance spectroscopy (MRS) measures the two most common inhibitory and excitatory neurotransmitters, GABA and glutamate, in the human brain. However, the role of MRS-derived GABA and glutamate signals in relation to system-level neural signaling and behavior is not fully understood. In this study, we investigated levels of GABA and glutamate in the visual cortex of healthy human participants (both genders) in three functional states with increasing visual input. Compared with a baseline state of eyes closed, GABA levels decreased after opening the eyes in darkness and Glx levels remained stable during eyes open but increased with visual stimulation. In relevant states, GABA and Glx correlated with amplitude of fMRI signal fluctuations. Furthermore, visual discriminatory performance correlated with the level of GABA, but not Glx. Our study suggests that differences in brain states can be detected through the contrasting dynamics of GABA and Glx, which has implications in interpreting MRS measurements.
CRIS-Team Scopus Importer:2022-11-28
Keywords: fMRS; GABA; Glutamate; Rs-fMRI; Visual discriminatory performance; Visual system

Predicting effective connectivity from resting-state networks in healthy elderly and patients with prodromal Alzheimer's disease - Neufang, Susanne; Akhrif, Atae; Riedl, Valentin; Foerstl, Hans; Kurz, Alexander; Zimmer, Claus; Sorg, Christian; Wohlschlaeger, Afra M. (Human Brain Mapping, 2014)
Using functional neuroimaging techniques two aspects of functional integration in the human brain have been investigated, functional connectivity and effective connectivity. In this study we examined both connectivity types in parallel within an executive attention network during rest and while performing an attention task. We analyzed the predictive value of resting-state functional connectivity on task-induced effective connectivity in patients with prodromal Alzheimer's disease (AD) and healthy elderly. We found that in healthy elderly, functional connectivity was a significant predictor for effective connectivity, however, it was frequency-specific. Effective top-down connectivity emerging from prefrontal areas was related with higher frequencies of functional connectivity (e.g., 0.08-0.15 Hz), in contrast to effective bottom-up connectivity going to prefrontal areas, which was related to lower frequencies of functional connectivity (e.g., 0.001-0.03 Hz). In patients, the prediction of effective connectivity by functional connectivity was disturbed. We conclude that functional connectivity and effective connectivity are interrelated in healthy brains but this relationship is aberrant in very early AD. © 2013 Wiley Periodicals, Inc.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Effective connectivity; Executive attention network; Prodromal Alzheimer's disease; Resting-state functional connectivity

Prediction of Alzheimer's disease using individual structural connectivity networks - Shao, Junming; Myers, Nicholas; Yang, Qinli; Feng, Jing; Plant, Claudia; Boehm, Christian; Foerstl, Hans; Kurz, Alexander; Zimmer, Claus; Meng, Chun; Riedl, Valentin; Wohlschlaeger, Afra; et al. (Neurobiology of aging, 2012)
Alzheimer's disease (AD) progressively degrades the brain's gray and white matter. Changes in white matter reflect changes in the brain's structural connectivity pattern. Here, we established individual structural connectivity networks (ISCNs) to distinguish predementia and dementia AD from healthy aging in individual scans. Diffusion tractography was used to construct ISCNs with a fully automated procedure for 21 healthy control subjects (HC), 23 patients with mild cognitive impairment and conversion to AD dementia within 3 years (AD-MCI), and 17 patients with mild AD dementia. Three typical pattern classifiers were used for AD prediction. Patients with AD and AD-MCI were separated from HC with accuracies greater than 95% and 90%, respectively, irrespective of prediction approach and specific fiber properties. Most informative connections involved medial prefrontal, posterior parietal, and insular cortex. Patients with mild AD were separated from those with AD-MCI with an accuracy of approximately 85%. Our finding provides evidence that ISCNs are sensitive to the impact of earliest stages of AD. ISCNs may be useful as a white matter-based imaging biomarker to distinguish healthy aging from AD. © 2012 Elsevier Inc..
CRIS-Team Scopus Importer:2022-11-28
Keywords: Alzheimer's disease; Classification; Diffusion tractography; Structural connectivity

Repeated pain induces adaptations of intrinsic brain activity to reflect past and predict future pain - Riedl, Valentin; Valet, Michael; Woeller, Andreas; Sorg, Christian; Vogel, Dominik; Sprenger, Till; Boecker, Henning; Wohlschlaeger, Afra M.; Toelle, Thomas R. (NeuroImage, 2011)
Recent neuroimaging studies have revealed a persistent architecture of intrinsic connectivity networks (ICNs) in the signal of functional magnetic resonance imaging (fMRI) of humans and other species. ICNs are characterized by coherent ongoing activity between distributed brain regions during rest, in the absence of externally oriented behavior. While these networks strongly reflect anatomical connections, the relevance of ICN activity for human behavior remains unclear. Here, we investigated whether intrinsic brain activity adapts to repeated pain and encodes an individual's experience. Healthy subjects received a short episode of heat pain on 11 consecutive days. Across this period, subjects either habituated or sensitized to the painful stimulation. This adaptation was reflected in plasticity of a sensorimotor ICN (SMN) comprising pain related brain regions: coherent intrinsic activity of the somatosensory cortex retrospectively mirrored pain perception; on day 11, intrinsic activity of the prefrontal cortex was additionally synchronized with the SMN and predicted whether an individual would experience more or less pain during upcoming stimulation. Other ICNs of the intrinsic architecture remained unchanged. Due to the ubiquitous occurrence of ICNs in several species, we suggest intrinsic brain activity as an integrative mechanism reflecting accumulated experiences. © 2011 Elsevier Inc.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Intrinsic brain activity; Intrinsic connectivity network; Learning; Memory; Pain; Plasticity; Prediction; Resting state

Resting-state fMRI evidence for early episodic memory consolidation: effects of age - Kukolja, Juraj; Goereci, D. Yasemin; Onur, Oezguer A.; Riedl, Valentin; Fink, Gereon R. (Neurobiology of aging, 2016)
Aging-related episodic memory decline is often attributed to insufficient encoding of new information, although the underlying neural processes remain elusive. We here tested the hypothesis that impaired memory consolidation contributes to aging-related memory decline. To this end, we used resting state functional magnetic resonance imaging in healthy young and older adults and investigated neural network connectivity underlying episodic memory consolidation and the effects of aging thereon. During postencoding rest, connectivity increased in subregions of temporobasal and temporo-occipital networks but decreased in a precuneal network. These connectivity changes predicted subsequent memory performance thereby constituting functional correlates of early memory consolidation. Furthermore, these consolidation-related regional connectivity changes partially overlapped with encoding-related neural activity changes, suggesting a close relationship between encoding- and consolidation-related activity. Older when compared to young participants failed to increase connectivity in the right lingual gyrus as part of an extended default mode network during consolidation, thereby providing a functional correlate for spatial contextual memory deficits. In conclusion, results are consistent with previous reports of persistent activity in regions mediating memory encoding as a core mechanism underlying episodic memory consolidation. Our data extend previous findings suggesting that aging-related memory decline results from a reduction of consolidation processes.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Aging; Independent component analysis; Retroactive interference; Source memory

Resting-state networks as simultaneously measured with functional MRI and PET - Savio, Alexandre; Fuenger, Sarah; Tahmasian, Masoud; Rachakonda, Srinivas; Manoliu, Andrei; Sorg, Christian; Grimmer, Timo; Calhoun, Vince; Drzezga, Alexander; Riedl, Valentin; Yakushev, Igor (Journal of Nuclear Medicine, 2017)
Functional MRI (fMRI) stuDies reported Disruption of resting-state networks (RSNs) in several neuropsychiatric Disorders. PET with 18F-FDG captures neuronal activity that is in steady state at a longer time span and is less dependent on neurovascular coupling. Methods: In the present study, we aimed to identify RSNs in 18F-FDG PET data and compare their spatial pattern with those obtained from simultaneously acquired resting-state fMRI data in 22 middle-aged healthy subjects. Results: Thirteen and 17 meaningful RSNs could be identified in PET and fMRI data, respectively. Spatial overlap was fair tomoderate for the defaultmode, left central executive, primary and secondary visual, sensorimotor, cerebellar, and auDitory networks. Despite recorDing Different aspects of neural activity, similar RSNs were detected by both imaging modalities. Conclusion: The results argue for the common neural substrate of RSNs and encourage testing of the clinical utility of resting-state connectivity in PET data.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Brain connectivity; Glucose metabolism; Independent component analysis; Multimodal imaging; Positron emission tomography

Shifted intrinsic connectivity of central executive and salience network in borderline personality disorder - Doll, Anselm; Sorg, Christian; Manoliu, Andrei; Woeller, Andreas; Meng, Chun; Foerstl, Hans; Zimmer, Claus; Wohlschloeger, Afra M.; Riedl, Valentin (Frontiers in Human Neuroscience, 2013)
Borderline personality disorder (BPD) is characterized by "stable instability" of emotions and behavior and their regulation. This emotional and behavioral instability corresponds with a neurocognitive triple network model of psychopathology, which suggests that aberrant emotional saliency and cognitive control is associated with aberrant interaction across three intrinsic connectivity networks [i.e., the salience network (SN), default mode network (DMN), and central executive network (CEN)]. The objective of the current study was to investigate whether and how such triple network intrinsic functional connectivity (iFC) is changed in patients with BPD. We acquired resting-state functional magnetic resonance imaging (rs-fMRI) data from 14 patients with BPD and 16 healthy controls. High-model order independent component analysis was used to extract spatiotemporal patterns of ongoing, coherent blood-oxygen-level-dependent signal fluctuations from rs-fMRI data. Main outcome measures were iFC within networks (intra-iFC) and between networks (i.e., network time course correlation inter-iFC). Aberrant intra-iFC was found in patients' DMN, SN, and CEN, consistent with previous findings. While patients' inter-iFC of the CEN was decreased, inter-iFC of the SN was increased. In particular, a balance index reflecting the relationship of CEN- and SN-inter-iFC across networks was strongly shifted from CEN to SN connectivity in patients. Results provide first preliminary evidence for aberrant triple network iFC in BPD. Our data suggest a shift of inter-network iFC from networks involved in cognitive control to those of emotion-related activity in BPD, potentially reflecting the persistent instability of emotion regulation in patients. © 2013 Doll, Sorg,Manoliu, Wöller,Meng, Förstl, Zimmer,Wohlschläger and Riedl.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Brain connectivity; Brain networks; Central executive network; Default mode network; Large-scale networks; Resting-state functional connectivity; Salience network; Triple network hypothesis

Simultaneous electroencephalographic and functional magnetic resonance imaging indicate impaired cortical top-down processing in association with anesthetic-induced unconsciousness - Jordan, Denis; Ilg, Ruediger; Riedl, Valentin; Schorer, Anna; Grimberg, Sabine; Neufang, Susanne; Omerovic, Adem; Berger, Sebastian; Untergehrer, Gisela; Preibisch, Christine; Schulz, Enrico; Schuster, Tibor; et al. (Anesthesiology, 2013)
Background: In imaging functional connectivity (FC) analyses of the resting brain, alterations of FC during unconsciousness have been reported. These results are in accordance with recent electroencephalographic studies observing impaired top-down processing during anesthesia. In this study, simultaneous records of functional magnetic resonance imaging between underlying physiological processes. The relationship (fMRI) and electroencephalogram were performed to investigate the causality of neural mechanisms during propofolinduced loss of consciousness by correlating FC in fMRI and directional connectivity (DC) in electroencephalogram. Methods: Resting-state 63-channel electroencephalogram and blood oxygen level-dependent 3-Tesla fMRI of 15 healthy subjects were simultaneously registered during consciousness and propofol-induced loss of consciousness. To indicate DC, electroencephalographic symbolic transfer entropy was applied as a nonlinear measure of mutual interdependencies between FC of resting-state networks of the brain (z values) and DC was analyzed by a partial correlation. Results: Independent component analyses of resting-state fMRI showed decreased FC in frontoparietal default networks during unconsciousness, whereas FC in primary sensory networks increased. DC indicated a decline in frontal-parietal (area under the receiver characteristic curve, 0.92; 95% CI, 0.68-1.00) and frontooccipital (0.82; 0.53-1.00) feedback DC (P < 0.05 corrected). The changes of FC in the anterior default network correlated with the changes of DC in frontal-parietal (rpartial = +0.62; P = 0.030) and frontal-occipital (+0.63; 0.048) electroencephalographic electrodes (P < 0.05 corrected). Conclusion: The simultaneous propofol-induced suppression of frontal feedback connectivity in the electroencephalogram and of frontoparietal FC in the fMRI indicates a fundamental role of top-down processing for consciousness. © 2013, the American Society of Anesthesiologists.
CRIS-Team Scopus Importer:2022-11-28

The lower hippocampus global connectivity, the higher its local metabolism in Alzheimer disease - Tahmasian, Masoud; Pasquini, Lorenzo; Scherr, Martin; Meng, Chun; Foerster, Stefan; Bratec, Satja Mulej; Shi, Kuangyu; Yakushev, Igor; Schwaiger, Markus; Grimmer, Timo; Diehl-Schmid, Janine; Riedl, Valentin; et al. (Neurology, 2015)
Objectives: Based on the hippocampus disconnection hypothesis in Alzheimer disease (AD), which postulates that uncoupling from cortical inputs contributes to disinhibition-like changes in hippocampus activity, we suggested that in patients with AD, the more the intrinsic functional connectivity between hippocampus and precuneus is decreased, the higher hippocampal glucose metabolism will be. Methods: Forty patients with mild AD dementia, 21 patients with mild cognitive impairment, and 26 healthy controls underwent simultaneous PET/MRI measurements on an integrated PET/MR scanner. 18 F-fluorodeoxyglucose-PET was used to measure local glucose metabolism as proxy for neural activity, and resting-state functional MRI with seed-based functional connectivity analysis was performed to measure intrinsic functional connectivity as proxy for neural coupling. Group comparisons and correlation analysis were corrected for effects of regional atrophy, partial volume effect, age, and sex. Results: In both patient groups, intrinsic connectivity between hippocampus and precuneus was significantly reduced. Moreover, in both patient groups, glucose metabolism was reduced in the precuneus (AD < mild cognitive impairment < controls) while unchanged in the hippocampus. Critically, the lower connectivity between hippocampus and precuneus was in patients with AD dementia, the higher was hippocampus metabolism. Conclusion: Results provide evidence that in patients with AD dementia, stronger decrease of intrinsic connectivity between hippocampus and precuneus is linked with higher intrahippocampal metabolism (probably reflecting higher neuronal activity). These data support the hippocampus disconnection hypothesis, i.e., uncoupling from cortical inputs may contribute to disinhibition-like changes of hippocampal activity with potentially adverse consequences on both intrahippocampal physiology and clinical outcome.
CRIS-Team Scopus Importer:2022-11-28

The physiological effects of noninvasive brain stimulation fundamentally differ across the human cortex - Castrillon, Gabriel; Sollmann, Nico; Kurcyus, Katarzyna; Razi, Adeel; Krieg, Sandro M.; Riedl, Valentin (Science Advances, 2020)
Transcranial magnetic stimulation (TMS) is a noninvasive method to modulate brain activity and behavior in humans. Still, stimulation effects substantially vary across studies and individuals, thereby restricting the large-scale application of TMS in research or clinical settings. We revealed that low-frequency stimulation had opposite impact on the functional connectivity of sensory and cognitive brain regions. Biophysical modeling then identified a neuronal mechanism underlying these region-specific effects. Stimulation of the frontal cortex decreased local inhibition and disrupted feedforward and feedback connections. Conversely, identical stimulation increased local inhibition and enhanced forward signaling in the occipital cortex. Last, we identified functional integration as a macroscale network parameter to predict the region-specific effect of stimulation in individual subjects. In summary, we revealed how TMS modulation critically depends on the connectivity profile of target regions and propose an imaging marker to improve sensitivity of noninvasive brain stimulation for research and clinical applications.
CRIS-Team Scopus Importer:2022-11-28

Toward discovery science of human brain function - Biswal, Bharat B.; Mennes, Maarten; Zuo, Xi-Nian; Gohel, Suril; Kelly, Clare; Smith, Steve M.; Beckmann, Christian F.; Adelstein, Jonathan S.; Buckner, Randy L.; Colcombe, Stan; Dogonowski, Anne-Marie; Ernst, Monique; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Although it is being successfully implemented for exploration of the genome, discovery science has eluded the functional neuroimaging community. The core challenge remains the development of common paradigms for interrogating the myriad functional systems in the brain without the constraints of a priori hypotheses. Resting-state functional MRI (R-fMRI) constitutes a candidate approach capable of addressing this challenge. Imaging the brain during rest reveals large-amplitude spontaneous low-frequency (<0.1 Hz) fluctuations in the fMRI signal that are temporally correlated across functionally related areas. Referred to as functional connectivity, these correlations yield detailed maps of complex neural systems, collectively constituting an individual's "functional connectome." Reproducibility across datasets and individuals suggests the functional connectome has a common architecture, yet each individual's functional connectome exhibits unique features, with stable, meaningful interindividual differences in connectivity patterns and strengths. Comprehensive mapping of the functional connectome, and its subsequent exploitation to discern genetic influences and brain-behavior relationships, will require multicenter collaborative datasets. Here we initiate this endeavor by gathering R-fMRI data from 1,414 volunteers collected independently at 35 international centers. We demonstrate a universal architecture of positive and negative functional connections, as well as consistent loci of inter-individual variability. Age and sex emerged as significant determinants. These results demonstrate that independent R-fMRI datasets can be aggregated and shared. High-throughput R-fMRI can provide quantitative phenotypes for molecular genetic studies and biomarkers of developmental and pathological processes in the brain. To initiate discovery science of brain function, the 1000 Functional Connectomes Project dataset is freely accessible at www.nitrc.org/projects/fcon- 1000/.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Database; Neuroimaging; Open access; Reproducibility; Resting state

Transdiagnostic commonalities and differences in resting state functional connectivity of the default mode network in schizophrenia and major depression - Schilbach, Leonhard; Hoffstaedter, F.; Mueller, V.; Cieslik, E. C.; Goya-Maldonado, R.; Trost, Sarah; Sorg, C.; Riedl, Valentin; Jardri, Renaud; Sommer, Iris E; Kogler, L.; Derntl, B.; et al. (NeuroImage: Clinical, 2016)
Schizophrenia and depression are prevalent psychiatric disorders, but their underlying neural bases remains poorly understood. Neuroimaging evidence has pointed towards the relevance of functional connectivity aberrations in default mode network (DMN) hubs, dorso-medial prefrontal cortex and precuneus, in both disorders, but commonalities and differences in resting state functional connectivity of those two regions across disorders has not been formally assessed. Here, we took a transdiagnostic approach to investigate resting state functional connectivity of those two regions in 75 patients with schizophrenia and 82 controls from 4 scanning sites and 102 patients with depression and 106 controls from 3 sites. Our results demonstrate common dysconnectivity patterns as indexed by a significant reduction of functional connectivity between precuneus and bilateral superior parietal lobe in schizophrenia and depression. Furthermore, our findings highlight diagnosis-specific connectivity reductions of the parietal operculum in schizophrenia relative to depression. In light of evidence that points towards the importance of the DMN for social cognitive abilities and well documented impairments of social interaction in both patient groups, it is conceivable that the observed transdiagnostic connectivity alterations may contribute to interpersonal difficulties, but this could not be assessed directly in our study as measures of social behavior were not available. Given the operculum's role in somatosensory integration, diagnosis-specific connectivity reductions may indicate a pathophysiological mechanism for basic self-disturbances that is characteristic of schizophrenia, but not depression.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Default mode network; fMRI; Major depression; Resting state functional connectivity; Schizophrenia; Transdiagnostic analysis

Utilization of hybrid PET/MR in neuroimaging - Tahmasian, Masoud; Eggers, Carsten; Riedl, Valentin; Sorg, Christian; Drzezga, Alexander (Basic and Clinical Neuroscience, 2015)
CRIS-Team Scopus Importer:2022-11-28

Visual imagery and functional connectivity in blindness: a single-case study - Boucard, Christine C.; Rauschecker, Josef P.; Neufang, Susanne; Berthele, Achim; Doll, Anselm; Manoliu, Andrej; Riedl, Valentin; Sorg, Christian; Wohlschlaeger, Afra; Muehlau, Mark (Brain Structure & Function, 2016)
We present a case report on visual brain plasticity after total blindness acquired in adulthood. SH lost her sight when she was 27. Despite having been totally blind for 43 years, she reported to strongly rely on her vivid visual imagery. Three-Tesla magnetic resonance imaging (MRI) of SH and age-matched controls was performed. The MRI sequence included anatomical MRI, resting-state functional MRI, and task-related functional MRI where SH was instructed to imagine colours, faces, and motion. Compared to controls, voxel-based analysis revealed white matter loss along SH’s visual pathway as well as grey matter atrophy in the calcarine sulci. Yet we demonstrated activation in visual areas, including V1, using functional MRI. Of the four identified visual resting-state networks, none showed alterations in spatial extent; hence, SH’s preserved visual imagery seems to be mediated by intrinsic brain networks of normal extent. Time courses of two of these networks showed increased correlation with that of the inferior posterior default mode network, which may reflect adaptive changes supporting SH’s strong internal visual representations. Overall, our findings demonstrate that conscious visual experience is possible even after years of absence of extrinsic input.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Adulthood; Blindness; Neuroplasticity; Visual system

Within-patient correspondence of amyloid-β and intrinsic network connectivity in Alzheimer's disease - Myers, Nicholas; Pasquini, Lorenzo; Goettler, Jens; Grimmer, Timo; Koch, Kathrin; Ortner, Marion; Neitzel, Julia; Muehlau, Mark; Foerster, Stefan; Kurz, Alexander; Foerstl, Hans; Zimmer, Claus; et al. (Brain, 2014)
There is striking overlap between the spatial distribution of amyloid-β pathology in patients with Alzheimer's disease and the spatial distribution of high intrinsic functional connectivity in healthy persons. This overlap suggests a mechanistic link between amyloid-β and intrinsic connectivity, and indeed there is evidence in patients for the detrimental effects of amyloid-β plaque accumulation on intrinsic connectivity in areas of high connectivity in heteromodal hubs, and particularly in the default mode network. However, the observed spatial extent of amyloid-β exceeds these tightly circumscribed areas, suggesting that previous studies may have underestimated the negative impact of amyloid-β on intrinsic connectivity. We hypothesized that the known positive baseline correlation between patterns of amyloid-β and intrinsic connectivity may mask the larger extent of the negative effects of amyloid-β on connectivity. Crucially, a test of this hypothesis requires the within-patient comparison of intrinsic connectivity and amyloid-β distributions. Here we compared spatial patterns of amyloid-β-plaques (measured by Pittsburgh compound B positron emission tomography) and intrinsic functional connectivity (measured by resting-state functional magnetic resonance imaging) in patients with prodromal Alzheimer's disease via spatial correlations in intrinsic networks covering fronto-parietal heteromodal cortices. At the global network level, we found that amyloid-β and intrinsic connectivity patterns were positively correlated in the default mode and several fronto-parietal attention networks, confirming that amyloid-β aggregates in areas of high intrinsic connectivity on a within-network basis. Further, we saw an internetwork gradient of the magnitude of correlation that depended on network plaque-load. After accounting for this globally positive correlation, local amyloid-β-plaque concentration in regions of high connectivity co-varied negatively with intrinsic connectivity, indicating that amyloid-β pathology adversely reduces connectivity anywhere in an affected network as a function of local amyloid-β-plaque concentration. The local negative association between amyloid-β and intrinsic connectivity was much more pronounced than conventional group comparisons of intrinsic connectivity would suggest. Our findings indicate that the negative impact of amyloid-β on intrinsic connectivity in heteromodal networks is underestimated by conventional analyses. Moreover, our results provide first within-patient evidence for correspondent patterns of amyloid-β and intrinsic connectivity, with the distribution of amyloid-β pathology following functional connectivity gradients within and across intrinsic networks. © 2014 The Author.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Alzheimer's disease; amyloid-β plaques; intrinsic connectivity; PiB-PET; resting-state functional MRI